FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN UMUM PERDANA DI BURSA EFEK INDONESIA TAHUN 2012-2015 - Inten Palupi, 13.05.52.0180; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of underwriter’s reputation, corporate profitability (ROA), financial leverage (DER), firm’s scale and firm’s age on the level of underpricing with the case study companies on the Stock Exchange Indonesia periode from 2012 to 2015. The research used purposive sampling method . Secondary datas were used and obtained from the Indonesian Stock Exchange by using Multiple Regression analysis testing to prove the research’s hypothesis. The results shows that the underwriter's reputation, corporate profitability (ROA), and financial leverage (DER) affected the underpricing negatively. The scale of companies affected on the level of underpricing positively and the firm’s age do not significantly affected the level of underpricing.Keywords: Underpricing, Underwriter’s Reputation, Corporate Profitability (ROA), Financial Leverage (DER), Firm’s Scale and Firm’s Age